2014
DOI: 10.3389/fchem.2014.00070
|View full text |Cite
|
Sign up to set email alerts
|

Protein disulfide isomerase a multifunctional protein with multiple physiological roles

Abstract: Protein disulfide isomerase (PDI), is a member of the thioredoxin superfamily of redox proteins. PDI has three catalytic activities including, thiol-disulfide oxireductase, disulfide isomerase and redox-dependent chaperone. Originally, PDI was identified in the lumen of the endoplasmic reticulum and subsequently detected at additional locations, such as cell surfaces and the cytosol. This review will provide an overview of the recent advances in relating the structural features of PDI to its multiple catalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(116 citation statements)
references
References 93 publications
(145 reference statements)
4
112
0
Order By: Relevance
“…Two broad categories of PDI assays have been employed [9,12,32,43,47,48]. The first involves the ability of PDI to catalyze the isomerization of mispaired disulfides in peptides and proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Two broad categories of PDI assays have been employed [9,12,32,43,47,48]. The first involves the ability of PDI to catalyze the isomerization of mispaired disulfides in peptides and proteins.…”
Section: Resultsmentioning
confidence: 99%
“…PDI is localized in the lumen of the endoplasmic reticulum (ER) as well as the cell surface and cytosol. Recent studies revealed that PDI, through its thiol redox activity, plays a role in pathogenesis, promotes increased ROS in cells and protein aggregation . It is known that covalent modification of PDI hinders its normal function in specific pathologies such as cancer, neurodegenerative disorders, cardiovascular and infectious diseases .…”
Section: Resultsmentioning
confidence: 99%
“…However, once nitrosylated, the chaperone and isomerase activities of these proteins are attenuated markedly, reducing the efficacy of this defensive strategy [78]. This has particularly serious consequences as misfolded proteins are a source of free radical damage in their own right, and hence, the loss of the protein disulfide isomerase defense leads to further exacerbation of O&NS within the cellular environment [113,114]. It is also clear that excessive nitrosylation of single proteins can lead to serious pathology.…”
Section: Hypernitrosylation and Pathologymentioning
confidence: 95%